In Situ EC-EPR Spectroscopy and DFT Analysis of HUPD on Polycrystalline Pt - Götz, Rainer; Pyyhtiä, Kimmo; Li, Bingxin; Sarpey, Theophilus K.; Song, Kun-Ting; Todorova, Mira; Kukharchyk, Nadezhda; Schreier, Siegfried; Peljo, Pekka; Gubanova, Elena L.; Neugebauer, Jörg; Bandarenka, Aliaksandr S. (Wiley-VCH, 2026)
Electrochemical hydrogen production and conversion using renewable energy sources have become a key topic in catalysis research. Platinum and Pt-group metals are among the best materials promoting H2 evolution (HER) and oxidation (HOR) reactions. However, the nature of active surface sites should be further elucidated to improve their performance and gain a better fundamental understanding of those processes. This is not a trivial task, mainly due to the high surface mobility of the H-species. Here, we use in situ electron paramagnetic resonance (EPR) spectroscopy to investigate the Pt surface in the so-called underpotential deposition (UPD) region in acidic media and observe EPR responses indicative of hydrogen adsorption sites, the knowledge of which is essential for both HOR and HER. Our EPR measurements and theoretical ab initio molecular dynamics (AIMD) calculations suggest that the average adsorption sites for atomic hydrogen at the surface of platinum are either on-top sites or 3-fold hollow sites, while bridge sites are not likely to be occupied. For EPR, the intensity maximum is reached at −0.85 V versus Pt, and then the signal intensity vanishes for potentials just before HER, suggesting EPR-silent H2 formation. At the same time, ab initio density functional theory (DFT) calculations of a Pt(111) surface with 7/12 ML coverage of H at room temperature yield occupancy probabilities of 0.72 (fcc hollow), 0.26 (on-top), and 0 (bridge) for the respective sites. Hence, fcc hollow is favored over on-top adsorption sites at high coverages, which is consistent with the observation via EPR spectroscopy. To our knowledge, EPR spectroscopy was used for the first time to probe the EPR response during hydrogen electrosorption in the HUPD region at polycrystalline platinum electrodes in acidic electrolytes.